Potential shared therapeutic and hepatotoxic mechanisms of Tripterygium wilfordii polyglycosides treating three kinds of autoimmune skin diseases by regulating IL-17 signaling pathway and Th17 cell differentiation. (5th October 2022) - Chen, Yi; Wang, Yong-Fang; Song, Sha-Sha; Zhu, Jia; Wu, Li-Li; Li, Xin-Yu
Abstract: Ethnopharmacological relevance: Tripterygium wilfordii polyglycosides (TWP) are extracted from Tripterygium wilfordii Hook. f., which has the significant effects of anti-inflammation and immunosuppression and has been widely used to treat autoimmune diseases in traditional Chinese medicine. Aim of study: In Chinese clinical dermatology, TWP was generally used for the treatment of autoimmune skin diseases including psoriasis (PSO), systemic lupus erythematosus (SLE) and pemphigus (PEM). However, the potential hepatotoxicity (HPT) induced by TWP was also existing with the long-term use of TWP. This study aims to explore the potential shared therapeutic mechanism of TWP treating PSO, SLE, PEM and the possible hepatotoxic mechanism induced by TWP. Materials and methods: Network pharmacology was used to predict the potential targets and pathways in this study. The main bioactive compounds in TWP was screened according to TCMSP, PubChem, ChEMBL databases and Lipinski's Rule of Five. The potential targets of these chemical constituents were obtained from PharmMapper, SEA and SIB databases. The related targets of PSO, SLE, PEM and HPT were collected from GeneCards, DrugBank, DisGeNET and CTD databases. The target network construction was performed through STRING database and Cytoscape. GO enrichment, KEGG enrichment and molecular docking were then performed, respectively. In particular, imiquimod (IMQ)-induced PSO model was selected as the representative for the experimental verification of effects and shared therapeutic mechanisms of TWP. Results: 41 targets were considered as the potential shared targets of TWP treating PSO, SLE and PEM. KEGG enrichment indicated that IL-17 signaling pathway and Th17 cell differentiation were significant in the potential shared therapeutic mechanism of TWP. The animal experimental verification demonstrated that TWP could notably ameliorate skin lesions ( P ˂0.001), decrease inflammatory response ( P ˂0.05, P ˂0.01, P ˂0.001) and inhibit the differentiation of Th1/Th17 cells ( P ˂0.05, P ˂0.01) compared to PSO model group. The molecular docking and qPCR validation then showed that TWP could effectively act on MAPK14, IL-2, IL-6 and suppress Th17 cell differentiation and IL-17 signaling pathway. The possible hepatotoxic mechanism of TWP indicated that there were 145 hepatotoxic targets and it was also associated with IL-17 signaling pathway and Th17 cell differentiation, especially for the key role of ALB, CASP3 and HSP90AA1. Meanwhile, the potential correlations between efficacy and hepatotoxicity of TWP showed that 28 targets were shared by therapeutic and hepatotoxic mechanisms such as IL-6, IL-2, MAPK14, MMP9, ALB, CASP3 and HSP90AA1. These significant relevant targets were also involved in IL-17 signaling pathway and Th17 cell differentiation. Conclusions: There were shared disease targets in PSO, SLE and PEM, and TWP could treat them by potential shared therapeutic mechanisms of suppressing IL-17 signaling pathway and Th17 cell differentiation. The possible hepatotoxicity induced by TWP was also significantly associated with the regulation of IL-17 signaling pathway and Th17 cell differentiation. Meanwhile, the potential correlations between efficacy and hepatotoxicity of TWP also mainly focused on IL-17 signaling pathway and Th17 cell differentiation, which provided a potential direction for the study of the mechanism of "You Gu Wu Yun" theory of TWP treating autoimmune skin diseases in the future. Graphical abstract: Image 1